Smart Box Learning Media Based on Problem Based Learning to Improve Science Environmental Learning Outcomes - Maryana; Desi Wulandari (Jurnal Penelitian Pendidikan IPA, 2024)
The problems in this research are teachers' obstacles in creating concrete learning media, the problem-based learning model is less effective, and student learning outcomes are low in Environmental Science subjects. This research aims to: develop a design; test validity; and test the effectiveness of smart box learning media based on Problem Based Learning. The research method is a research and development method with a model developed by Sugiyono. The subjects in the research were media and material expert validators, students, and class V teachers at SD Negeri Wonosari 01. Data collection techniques were observation activities, interviews, document data analysis, questionnaires, validation sheets, and tests. The research results showed that the design of smart box learning media based on Problem Based Learning pays attention to the needs of teachers and students in learning activities; product validity obtained a percentage of 87.5% from media expert validators with very valid criteria and 88.75% from expert validators material with very valid criteria; and product effectiveness using the paired sample t-test, namely the calculated t result is 10.69 and the significance value is 0.00 so that there is a difference in the average pretest and posttest scores. The N-Gain test result was 0.54 with moderate criteria so that there was an increase in the average pretest and posttest scores.